Hydrolytic kinetic resolution as an emerging tool in the synthesis of bioactive molecules - Kumar, Pradeep; Gupta, Priti (Synlett, 2009)
A variety of racemic epoxides mainly derived from terminal olefins, such as aliphatic epoxides, multifuncitonalized epoxides and amine-substituted epoxides, have been successfully resolved into the enantiomerically pure epoxides and diols using Jacobsen's hydrolytic kinetic resolution (HKR) method. The chiral epoxides thus prepared were further elaborated by synthetic manipulation to provide a variety Of Compounds of biological interest. A general synthetic strategy for the construction Of S synlanti-1,3-polyol systems using iterative HKR has been developed, which was subsequently utilized in the synthesis of natural products with a broad range of biological activity. The protocol for the 1,3-polyols was also further extended to the synthesis of 1,3-amino alcohols.
Keywords: Biological activity; Hydrolytic kinetic resolution; Natural products; synthesis; terminal epoxides

Highly selective claisen-schmidt condensation catalyzed by silica chloride under solvent-free reaction conditions - Hazarkhani, Hassan; Kumar, Pradeep; Kondiram, Kadam Sachin; Gadwal, Ikhlas M. Shafi (Synthetic Communications, 2010)
Silica chloride serves as a useful catalyst in the cross-aldol condensation, leading to the synthesis of a wide variety of bisarylidene cycloalkanones and chalcones. The catalyst showed high selectivity; self-condensation of ketones was not observed.
Keywords: Aldol reaction; arylidene cycloalkanone; Claisen-Schmidt; condensation; silica chloride

Highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of alpha-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, Menaka; Chowdhury, Partha Sarathi; Dutta, Achintya Kumar; Kumar, Pradeep; Pal, Sourav (RSC Advances, 2013)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed alpha-amination of aldehyde and one-pot indium mediated allylation of the crude alpha-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.

Highly active recyclable SBA-15-EDTA-Pd catalyst for Mizoroki-Heck, Stille and Kumada C-C coupling reactions - Rathod, Jayant; Sharma, Priti; Pandey, Punam; Singh, A. P.; Kumar, Pradeep (Journal of Porous Materials, 2017)
Highly efficient SBA-15-EDTA-Pd(11) heterogeneous catalyst was synthesized by covalent anchoring Pd-EDTA complex over organo-modified surface of SBA-15. SBA-15-EDTA-Pd(11) catalyst was found to exhibit excellent catalytic activity in appreciable yield for Heck, Stille and Kumada cross-coupling reactions. Catalytic system exhibited excellent activity for completion of reaction, isolation, Pd loading (0.87 mmol%) and yields of products as compared to earlier reported heterogeneous supported Pd catalysts. Covalently anchored heterogeneous SBA-15-EDTA-Pd(11) catalyst can be recycled for more than five times without noticeable loss in activity and selectivity.

Harnessing nucleophilicity of allenol ester with p-quinone methides via gold catalysis: application to the synthesis of diarylmethine-substituted enones - Sharma, Brijesh M.; Rathod, Jayant; Gonnade, Rajesh G.; Kumar, Pradeep (Journal of Organic Chemistry, 2018)
A gold(I)-catalyzed protocol for intermolecular 1,6-conjugate addition of nucleophilic allenol ester generated in situ through [3,3]-sigmatropic rearrangement with p-quinone methides (p-QMs) has been developed. The gold catalyst plays a dual role by the pi-acid-triggered activation of alkynes and at the same time as a Lewis acid for activation of p-QMs toward nucleophilic attack. This method enables rapid access to a wide range of densely functionalized diarylmethine-substituted enones, a Morita-Baylis-Hillman (MBH) product with high selectivity, excellent yields, and broad substrate scope.

H5IO6, as an efficient reagent for the aromatization of tetrahydro-β-carbolines: total synthesis of norharman, harmane, harmine, kumujian-C, and orthoscuticellines B - Sabane, Jagjivan K.; Gaikwad, Sunil V.; Gajbhiye, Jayant M.; Kumar, Pradeep (ChemistrySelect, 2026)
A new method is reported for the synthesis of beta-carbolines and their derivatives using H5IO6 in DMSO solvent. The method is mild and efficient for oxidative decarboxylation and aromatization of tetrahydro beta-carbolines (TH beta C), resulting in good to excellent yields (70% to 88%) of beta-carbolines. This protocol has further been utilized for the synthesis of beta-carbolines based natural products, for examples, norharmane, harmane, harmine, Kumujian-C, and Orthoscuticellines A and B.
Keywords: aromatization; beta-carboline; H5IO6; Harmine; orthoscuticellines; Oxidative